2016
DOI: 10.4167/jbv.2016.46.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coagulation Factor 2 Receptor during Respiratory Pneumococcal Infections

Abstract: Coagulation factor 2 receptor (F2R), also well-known as a protease-activated receptor 1 (PAR1), is the first known thrombin receptor and plays a critical role in transmitting thrombin-mediated activation of intracellular signaling in many types of cells. It has been known that bacterial infections lead to activation of coagulation systems, and recent studies suggest that PAR1 may be critically involved not only in mediating bacteria-induced detrimental coagulation, but also in innate immune and inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Coagulation factor 2 receptor (F2R), also well-known as a protease-activated receptor 1 (PAR1), is the rst known thrombin receptor and plays a critical role in transmitting thrombin-mediated activation of intracellular signalling in many types of cells. Recent studies have suggested that F2R may be critically involved not only in mediating bacteria-induced detrimental coagulation but also in innate immune and in ammatory responses 24 . Other studies have suggested that F2R might be used as an adipogenic marker to provide a potential target for understanding metabolic syndromes such as obesity, type-2 diabetes, and atherosclerosis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation factor 2 receptor (F2R), also well-known as a protease-activated receptor 1 (PAR1), is the rst known thrombin receptor and plays a critical role in transmitting thrombin-mediated activation of intracellular signalling in many types of cells. Recent studies have suggested that F2R may be critically involved not only in mediating bacteria-induced detrimental coagulation but also in innate immune and in ammatory responses 24 . Other studies have suggested that F2R might be used as an adipogenic marker to provide a potential target for understanding metabolic syndromes such as obesity, type-2 diabetes, and atherosclerosis 25 .…”
Section: Discussionmentioning
confidence: 99%